An approximate approach to sample size determination in bioequivalence testing with multiple pharmacokinetic responses. (28th April 2014) - Tsai, Chen‐An; Huang, Chih‐Yang; Liu, Jen‐pei
<x xml:space="preserve">Abstract</x> The approval of generic drugs requires the evidence of average bioequivalence (ABE) on both the area under the concentration–time curve and the peak concentration Cmax. The bioequivalence (BE) hypothesis can be decomposed into the non‐inferiority (NI) and non‐superiority (NS) hypothesis. Most of regulatory agencies employ the two one‐sided tests (TOST) procedure to test ABE between two formulations. As it is based on the intersection–union principle, the TOST procedure is conservative in terms of the type I error rate. However, the type II error rate is the sum of the type II error rates with respect to each null hypothesis of NI and NS hypotheses. When the difference in population means between two treatments is not 0, no close‐form solution for the sample size for the BE hypothesis is available. Current methods provide the sample sizes with either insufficient power or unnecessarily excessive power. We suggest an approximate method for sample size determination, which can also provide the type II rate for each of NI and NS hypotheses. In addition, the proposed method is flexible to allow extension from one pharmacokinetic (PK) response to determination of the sample size required for multiple PK responses. We report the results of a numerical study. An R code is provided to calculate the sample size for BE testing based on the proposed methods. Copyright © 2014 John Wiley & Sons, Ltd.